The returns to education: A meta-study - Gregory Clark; Christian Alexander Abildgaard Nielsen (European Historical Economics Society (EHES), 2024)
There have been many studies estimating the causal effect of an additional year of education on earnings. The majority employ administrative changes in the minimum school leaving age as the mechanism allowing identification. Here we survey 66 such estimates. However, remarkably, while the majority of these studies find substantial gains from education, a number of well-grounded studies find no effect. The average return from these studies still implies substantial average gains from an extra year of education: an average of 8.5%. But the pattern of reported returns shows clear evidence of publication biases. There is, in particular, large scale omission of studies showing negative return estimates. Correcting for these omitted studies, the implied average causals returns to an extra year of schooling are close to 0.
Keywords: I26; J24; N3; 330; human capital; returns to education; publication bias